2022
DOI: 10.3389/pore.2022.1610645
|View full text |Cite
|
Sign up to set email alerts
|

Pomalidomide Treatment in Relapsed/Refractory Multiple Myeloma Patients—Real-World Data From Hungary

Abstract: Pomalidomide is a third generation immunomodulatory drug in the treatment of refractory and relapsed multiple myeloma patients. Our aim was to investigate the efficacy and safety of pomalidomide therapy in a real world setting. Eighty-six Hungarian patients were included, 45 of whom received pomalidomide ± an alkylating agent, while in 38 of them pomalidomide was combined with a proteasome inhibitor. 56 patients (65%) showed any response to the treatment with 18 complete or very good partial remissions and 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…We found that the outcomes of Pd, the ≥ PR rate of 35.8%, and the median TNT of 4.9 months were similar to those reported in previous studies [8][9][10][11][12][13][14][15]. Most notably, the clinical performance of Pd in our study was almost identical to that achieved in prospective clinical trials, which is typically not the case when prospective and real-world studies are compared [2,16,17,19].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We found that the outcomes of Pd, the ≥ PR rate of 35.8%, and the median TNT of 4.9 months were similar to those reported in previous studies [8][9][10][11][12][13][14][15]. Most notably, the clinical performance of Pd in our study was almost identical to that achieved in prospective clinical trials, which is typically not the case when prospective and real-world studies are compared [2,16,17,19].…”
Section: Discussionsupporting
confidence: 87%
“…Pomalidomide‐dexamethasone (Pd) has since been tested in triplet combinations with other antimyeloma agents and is currently approved for relapsed and refractory multiple myeloma in combination with bortezomib, daratumumab, isatuximab, or elotuzumab [3–7]. The outcomes of patients treated with Pd have been reported in several real‐world studies performed in smaller populations [8–15]. Recently, two novel antimyeloma drugs, the peptide‐conjugated alkylator melflufen in combination with dexamethasone, and the drug–antibody conjugate belantamab‐mafodotin both failed to prove superior to Pd in their respective randomized phase III trials [16, 17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median PFS and OS were 10.0 and 14.0 months, respectively. In addition, a recent report based on real-world data from Hungary indicated a median PFS and OS of 9.0 and 16.5 months, respectively [ 27 ] The results were quite optimistic because the study group was heavily pretreated with a median of 4 prior therapy lines. However, almost all patients in this cohort received pomalidomide in combination with an alkylating agent or a proteasome inhibitor.…”
Section: Discussionmentioning
confidence: 99%